Acid-mediated green synthesis and optimization of the calcium-terephthalate metal-organic framework derived from waste eggshells - Langmi, Henrietta Wakuna (University of Pretoria, 2023)
Dissertation (MSc (Chemistry))--University of Pretoria, 2023.